Empowering Undergraduates in Empirical Research Methods: an Experience Report - Vilela, Jéssyka; Silva, Carla (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2024.3549, 2024)
Context: Undergraduate students often struggle with research methods and methodologies crucial for their development. Effective training is essential to bridge the gap between theory and practice. Objective: This course aimed to empower students with a solid understanding of scientific research, enhance their research planning skills and proficiency in empirical methods, and improve their scientific writing and presentation skills. Method: An in-person Empirical Software Engineering course was conducted for 17 undergraduates over 60 hours in a semester. It included theoretical classes, practical activities, seminars, evaluations of empirical articles, and peer evaluations of research projects. Results: Students reported high satisfaction with the course, particularly in topic approach, content references, and achieving objectives. Areas for improvement included clarity of course objectives and developing critical thinking skills. Most activities were found useful, though some were challenging. Conclusions: The course successfully developed research skills among students. Improving clarity of objectives and support for complex activities can further enhance the learning experience. This report provides insights into empirical research education in software engineering, highlighting successes and areas for improvement.